Extensively drug-resistant tuberculosis as a cause of death in patients co-infected with tuberculosis and HIV in a rural area of South Africa. - Gandhi, Neel R; Moll, Anthony; Sturm, A Willem; Pawinski, Robert; Govender, Thiloshini; Lalloo, Umesh; Zeller, Kimberly; Andrews, Jason; Friedland, Gerald (Lancet, 2006)
The epidemics of HIV-1 and tuberculosis in South Africa are closely related. High mortality rates in co-infected patients have improved with antiretroviral therapy, but drug-resistant tuberculosis has emerged as a major cause of death. We assessed the prevalence and consequences of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis in a rural area in KwaZulu Natal, South Africa.
Keywords: Adult; Aged; Anti-Retroviral Agents; Female; Genotype; HIV Infections; HIV-1; Humans; Male; Middle Aged; Mycobacterium tuberculosis; Population Surveillance; Prevalence; Rural Health; South Africa; Sputum; Tuberculosis, Multidrug-Resistant; Viral Load